From State-Building to Integration: A Comparative Analysis of Albania’s Strategies toward Neighbours and Great Powers (1920–1924 vs. Post-1990) - Myrta, Rexhina (Advances in Social Sciences Research Journal, 2025)
This article offers a comparative analysis of Albania’s foreign-policy behaviour during two structurally distinct periods: the formative years 1920–1924, marked by existential threats to sovereignty, and the post-1990 era, characterised by democratic transition and deep Euro-Atlantic integration. Drawing on extensive archival materials including documents from the Albanian State Archives, League of Nations records, Italian diplomatic correspondence and British Foreign Office files the study demonstrates that early Albanian diplomacy was shaped by acute geopolitical vulnerability, regional revisionism and limited administrative capacity. Albania relied heavily on the League of Nations, legal appeals and the strategic exploitation of great-power rivalries to counter Yugoslav, Greek and Italian pressures. In contrast, the post-1990 period reveals an environment transformed by institutional density and security guarantees. NATO membership, EU conditionality and strengthened bilateral partnerships (particularly with the United States, Italy and Turkey) have shifted Albania’s diplomacy from survival-driven improvisation to structured, rules-based engagement. Yet despite the profound systemic differences, the analysis identifies strong continuity in Albania’s strategic repertoire: reliance on multilateral institutions, diversification of alliances, and the internationalisation of disputes. The article argues that these long-term behavioural patterns reflect the enduring logic of small-state adaptation. By tracing how Albania moved from a contested periphery in the 1920s to an institutionalised Euro-Atlantic actor today, the study contributes to scholarship on small-state diplomacy, regional security and the role of international institutions in shaping foreign-policy trajectories. Methodologically, the article applies a structured comparative historical analysis across the two periods.The findings highlight that Albania’s strategic resilience derives less from material capabilities than from effective institutional anchoring and calibrated diplomatic balancing.